TAX AGGRESSIVENESS: FINANCIAL STATEMENT AGGRESSIVENESS AND MANAGERIAL OWNERSHIP IN BANKING COMPANIES IN INDONESIA - Ni Made Suwitri Parwati; Chalarce Totanan; Nurlaela Mapparessa; Andi Ainil Mufidah Tanra; Amirah; I Made Ari Kusuma; Ni Luh Dian Sundari Indah (Universitas La Tansa Mashiro, 2025)
The study was conducted to reveal the interaction between financial statement aggressiveness, managerial ownership, and tax aggressiveness. Through SEM-PLS analysis, using Warp-PLS V.8.0 software to obtain test results for each research variable. The study found a positive interaction between financial statement aggressiveness and managerial ownership on tax aggressiveness, indicating that companies exhibit higher levels of aggressiveness in preparing financial statements through creative accounting practices, earlier recognition of revenue, significant deferral of expenses, and the adoption of aggressive strategies in tax obligations. Furthermore, the higher the proportion of shares owned by company managers, the more likely the company is to adopt aggressive strategies. Therefore, this study emphasizes the importance of oversight by financial sector institutions such as the Financial Services Authority and the Directorate General of Taxes, as well as strengthening corporate governance to prevent risky aggressive practices and maintain the stability of the national financial system.